2007
DOI: 10.1158/0008-5472.can-06-3344
|View full text |Cite
|
Sign up to set email alerts
|

The Human Papillomavirus E6 Oncogene Dysregulates the Cell Cycle and Contributes to Cervical Carcinogenesis through Two Independent Activities

Abstract: Cervical cancer is a leading cause of death due to cancer among women worldwide. Using transgenic mice to dissect the contributions of the human papillomavirus (HPV) 16 E6 and E7 oncogenes in cervical cancer, E7 was identified previously to be the dominant oncogene. Specifically, when treated with exogenous estrogen for 6 months, E7 transgenic mice developed cancer throughout the reproductive tract, but E6 transgenic mice did not. E6 contributed to carcinogenesis of the reproductive tract, as E6/E7 double tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
154
0
8

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(178 citation statements)
references
References 49 publications
13
154
0
8
Order By: Relevance
“…During adolescence and pregnancy, the cervix is exposed to augmented levels of hormonal changes (Singer and Monaghan, 2000), in which oestrogen stimulation facilitates acidification of the vaginal cavity, a determinant of squamous metaplasia when the endocervical epithelial everts (Elson et al, 2000). When this oestrogen-stimulated metaplastic transformation occurs in the presence of HPV, the probability of cell transformation increases, resulting in neoplastic changes (Elson et al, 2000;Shai et al, 2007Shai et al, , 2008Hwang et al, 2009). This phenomenon is dependent primarily on parity, and is more likely to occur during the first pregnancy rather than subsequent pregnancies (Singer and Monaghan, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…During adolescence and pregnancy, the cervix is exposed to augmented levels of hormonal changes (Singer and Monaghan, 2000), in which oestrogen stimulation facilitates acidification of the vaginal cavity, a determinant of squamous metaplasia when the endocervical epithelial everts (Elson et al, 2000). When this oestrogen-stimulated metaplastic transformation occurs in the presence of HPV, the probability of cell transformation increases, resulting in neoplastic changes (Elson et al, 2000;Shai et al, 2007Shai et al, , 2008Hwang et al, 2009). This phenomenon is dependent primarily on parity, and is more likely to occur during the first pregnancy rather than subsequent pregnancies (Singer and Monaghan, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Co-carcinogen studies with chemical carcinogens or with oestrogen in these mice indicated that whereas E7 promotes immortalization, E6 promotes progression into full malignancy (Song et al, 2000;Riley et al, 2003;Brake and Lambert, 2005). In the reproductive tract, E6 has significantly weaker activity than E7 (Riley et al, 2003); however, after prolonged oestrogen treatment, cervical tumours did result, although this activity did not seem to require PDZ-binding capacity (Shai et al, 2007). Most importantly, however, the ability of E6 to cooperate with E7 in increasing tumour size and frequency, both in the cervix and at other tumour sites, was dependent upon the ability of E6 to bind to its PDZ domain-containing substrates (Nguyen et al, 2003;Shai et al, 2007Shai et al, , 2008.…”
Section: Biological Consequences Of Hpv E6 Interaction With Pdz-contamentioning
confidence: 99%
“…In the reproductive tract, E6 has significantly weaker activity than E7 (Riley et al, 2003); however, after prolonged oestrogen treatment, cervical tumours did result, although this activity did not seem to require PDZ-binding capacity (Shai et al, 2007). Most importantly, however, the ability of E6 to cooperate with E7 in increasing tumour size and frequency, both in the cervix and at other tumour sites, was dependent upon the ability of E6 to bind to its PDZ domain-containing substrates (Nguyen et al, 2003;Shai et al, 2007Shai et al, , 2008. Obviously, the prime candidates for these activities of E6 are those substrates implicated in the regulation of cell polarity (see below), but the dissection of which target(s) is involved will require further dissection of E6's PDZ-binding capacity, as well as the use of conditional knockout mice in some of the polarity candidates.…”
Section: Biological Consequences Of Hpv E6 Interaction With Pdz-contamentioning
confidence: 99%
“…However, a previous study suggested that HPV infection alone is insufficient for inducing cervical cancer (Shai et al, 2007) and malignant changes (Kim and Zhao, 2005). There is an urgent need to understand the molecular mechanisms governing cervical tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%